Sistem Absensi Menggunakan Teknologi Location Based Service (LBS) - Muhammad Dimyathi; Edy Santoso; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Unichem Candi Indonesia (UCI) is a consumer good company with salt consumption product branded "refina". In the management regulation of PT. UCI there is a procedure attendance hours work hours at 08.00 WIB and come home from work at 16.00 WIB for Monday to Friday, while on Saturday at 08.00 to 14.30 WIB. Currently the Presence Employee attendance process has been using the Fingerprint Presence machine. Every employee in and out of the office without exception marketing personnel must do the Presence. Given this rule, marketing personnel objected. Due to within one business day, marketing personnel can go in and out of the office more than 3 times. The problem that often happens is to forget to do Presence, so that marketing personnel get a reprimand from superiors and penalty sanctions. As a solution to the problems that occur, the need for Presensi applications using Location Based Service technology (LBS). Where this technology becomes efficient and effective when applied to problems in PT.UCI. By using this application, marketing personnel no longer need to do Presence via fingerprint machine, but only need to bring a smartphone device that has been installed this application. This app works based on where the employee is located. When the employee is in coordinate office area then Presence status is enter office, while when the employee is outside the office area Presence status is out of office. Benefits derived from the results of this study is the marketing force no longer need to do Presence through the device fingerprint machine, but simply bring the Android smartphone device that has been installed by this application, so it can be marketing presence in the field.detected Presence status when out of office. In addition, the management can monitor the location